Perspektif Kinerja Berbasis Gaya Kepemimpinan, Lingkungan Kerja, dan Budaya Organisasi - Anis Sholikhah; Abu Talkah (Universitas Islam Kadiri, 2021)
This study aimed to find out the perspective, the constraints and impacts of performance based on the leadership style, work environment and organizational culture in the KSP Setia Bhakti Kediri. This study was conducted using qualitative methods with descriptive research type. Methods of collecting data by interview, observation and documentation. The results showed that: Performance based leadership style in the KSP Setia Bhakti were the branch head was able to provided suggestions, created a sense of security, able to formulated institutional development plans, and prioritized deliberation in making decisions. Performance based on organizational culture was a disciplined employee in working by practicing the values ​​of organizational culture. Based on the work environment, there were two dimensions found; conformity and team spirits. The Obstacles in leadership-based performance were challenged in developed the quality and skills of employees. The obstacles in performance based on organizational culture were conflicts of interest and weak moral standards. The constraints in work environment-based performance were poor air circulation and the lack of facilities. The impact were the level of ability and knowledge of employees were better and the level of discipline was increased.